Kepiting massage effect on weight gain and illness in wasting toddlers - Ifayanti, Hikmah; Putri, Nopi Anggista; Puspita, Linda; Lestari, Eliya Septi (Science Midwifery, 2025)
Wasting is an acute form of malnutrition in children under five, marked by low weight-for-height (W/H < –2 SD). It increases the risk of infection, impaired immunity, growth delays, and mortality. In 2020, an estimated 45.4 million under-five children were wasted globally. In Indonesia, the prevalence in 2023 was 8.5%, with 7.3% in Lampung, 2.87% in Pringsewu, and 9.49% in Pekon Pamenang. One complementary approach to improve nutritional status is pijat kepiting (kepiting massage), a combination of acupressure and pediatric massage believed to enhance appetite, digestion, and immunity. This study assessed its effect on weight gain and illness frequency among wasted children under five. Methods: A quasi-experimental non-equivalent control group pretest–posttest design was applied to 20 wasted children divided into intervention and control groups. The intervention group received kepiting massage in addition to standard care. Results: Weight increased significantly in both groups but was greater in the intervention group (0.66 kg vs. 0.30 kg; p=0.002). Illness frequency decreased more sharply in the intervention group (1.5 to 0.3 episodes/month; p=0.010) than in the control group (2.5 to 1.9; p=0.014), with significant between-group differences (p=0.000). Conclusion: Kepiting massage effectively improves weight gain and reduces illness frequency among wasted children.